Development and properties of the parental support of leisure exploration measure. (1st January 2022) - Sharp, Erin Hiley; Palen, Lori-Ann; Coatsworth, J. Douglas
Abstract: Leisure figures prominently in adolescent identity work. This paper tested the psychometric properties and validity of a new measure, Parental Support of Leisure Exploration (PSLE). We used three distinct samples: college undergraduates ( n = 409, M age 19.4), high school students ( n = 70, M age 16.8), and middle school students ( n = 126, M age 14.05). Factor analysis indicated two factors: encouragement of autonomous exploration and parental control and intrusion. The PSLE autonomous exploration scale was correlated with developmental measures in the expected directions; however, the control and intrusion scale was not consistently correlated with these measures. In the high school sample, PSLE correlated with established measures of parenting, and after controlling for more general parenting, the PSLE scales explained additional, unique variance in identity. Results suggest that promoting parenting behaviors that encourage identity exploration through leisure experiences could be a promising avenue for fostering identity development.